Evaluasi Kinerja Penegakan Protokol Kesehatan Oleh Anggota Posko Merdeka di Masa Covid-19 Oleh Dinas Pemadam Kebakaran dan Penanggulangan Bencana Kota Palembang - Iskandar Suhardi; Mega Nugraha; Sunarto Sunarto (Parlementer : Jurnal Studi Hukum dan Administrasi Publik, 2024)
Iskandar Suhardi, Evaluation of Health Protocol Enforcement Performance by Members of the Merdeka Post during the Covid-19 Period by the Palembang City Fire and Disaster Management Service. This study aims to analyze the Performance Evaluation of Health Protocol Enforcement by Members of the Merdeka Post during the Covid-19 Period by the Palembang City Fire and Disaster Management Service. The study used qualitative methods with data collection techniques, namely observation, interviews and documentation. The results of the study show that in the application of the health protocol itself in a combined unit of several elements and agencies, it has several weaknesses, first from the community side who really underestimates the Corona virus, then from the officers themselves there is still minimal knowledge in providing education about the importance of complying with health protocol. The enforcement of health protocols did not go as expected, based on the health protocol policy itself, because there were several aspects, where in fact not all people believed in the existence of the corona virus, some even said that this corona was just a political conspiracy and the like, so that officers had difficulty in enforcement of health protocols. In 2020-2021 the health protocol policy is going quite well, people still have fear and vigilance about the spread of the corona virus, but in the course of time and being supported by people who have been vaccinated 1 and 2, it makes people feel safer, so that strict adherence to simple wearing a mask is no longer obeyed, not to mention other things such as washing hands and so on. The implementation of this health protocol policy has many obstacles and the weak side is public awareness and the pros and cons regarding the presence or absence of the corona virus, so that some people do not obey the applicable rules, and this makes it difficult for officers to carry out the policies that have been determined. So in this case the officer must have the right technique or method so that the implementation process can be easier.